Mengenal Computasional Thingking (Salah Satu Kompetensi Baru Dalam Kurikulum Merdeka 2022) - Yulita Puji Harti; Loesita Sari; Amanah Agustin; Budijanto Budijanto (IKIP Budi Utomo Malang, 2022)
The Indonesian Minister of Education, Culture, Research and Technology launched a new curriculum called the Independent Curriculum. at the Grow with Google event on 18 February 2022. The curriculum states that computational thinking is one of the new competencies that will be included in the Indonesian children's learning system. The background to this policy is the government's efforts to prepare young people who are digitally literate. Jeanette Wing called it one of the abilities that a person should have, besides the basic skills of reading, writing and arithmetic. The research method in this article is a literature review with a systematic mapping study method. The stages of the literature review are as follows: 1) The stages begin by searching Science Direct and Eric with the keywords Computational Thinking, 2) followed by narrowed keywords, namely Assessing Computational Thinking. 3) Pursing the number of articles obtained is adjusted to the application of computational thinking in Indonesia. 4) Make a Literature Review. Computational thinking is defined as a person's ability to be able to present a problem and a solution to that problem in an algorithmic statement that can be executed like a computer. Technically computational thinking involves four steps: 1) decomposition: problem decomposition, 2) Pattern Recognition: finding patterns, 3) abstraction, and 4) algorithm development. Computational Thinking is simply the thinking process involved in formulating problems and generating solutions in ways that humans or computers can understand. Developing the knowledge and dispositions necessary to understand and create with a computational mind is now a 21st century imperative.